Holliday junction-containing DNA structures persist in cells lacking Sgs1 or Top3 following exposure to DNA damage - Mankouri, Hocine W; Ashton, Thomas M; Hickson, Ian D (Proceedings of the National Academy of Sciences - PNAS, 2011)
The Sgs1-Rmi1-Top3 "dissolvasome" is required for the maintenance of genome stability and has been implicated in the processing of various types of DNA structures arising during DNA replication. Previous investigations have revealed that unprocessed (X-shaped) homologous recombination repair (HRR) intermediates persist when S-phase is perturbed by using methyl methanesulfonate (MMS) in Saccharomyces cerevisiae cells with impaired Sgs1 or Top3. However, the precise nature of these persistent DNA structures remains poorly characterized. Here, we report that ectopic expression of either of two heterologous and structurally unrelated Holliday junction (HJ) resolvases, Escherichia coli RusA or human GEN1(1-527), promotes the removal of these X-structures in vivo. Moreover, other types of DNA replication intermediates, including stalled replication forks and non-HRR-dependent X-structures, are refractory to RusA or GEN1(1-527), demonstrating specificity of these HJ resolvases for MMS-induced X-structures in vivo. These data suggest that the X-structures persisting in cells with impaired Sgs1 or Top3 contain HJs. Furthermore, we demonstrate that Sgs1 directly promotes X-structure removal, because the persistent structures arising in Sgs1-deficient strains are eliminated when Sgs1 is reactivated in vivo. We propose that HJ resolvases and Sgs1-Top3-Rmi1 comprise two independent processes to deal with HJ-containing DNA intermediates arising during HRR in S-phase.